On Depth Processing in the Production of the Ponzo Illusion: Two Problems and a Solution. (February 2013) - Parks, Theodore E
Certain phenomenological difficulties for the depth-processing/size-scaling theory of the Ponzo illusion can be resolved if those theoretical activities are carried out in Milner and Goodale's proposed vision-for-action cortical pathway.